COMPARISON OF TOTAL CHOLESTEROL LEVELS IN SAMPLES SERUM TO BE CHECKED IMMEDIATELY AND SERUM SAMPLE WHICH WAS POSTPONED FOR 7 DAYS IN THE REFRIGERATOR WITH A TEMPERATURE OF 2-8°C AT BHAYANGKARA HOSPITAL - Sri Miranda Maku; Muh. Rizman Naim; Laras Puspita Taib (Journal of Health, Technology and Science (JHTS), 2026)
Total cholesterol measurement is an essential laboratory examination for assessing cardiovascular risk and monitoring lipid metabolism. However, immediate analysis is not always feasible in routine clinical practice, making refrigerated storage a common pre-analytical procedure. This study aimed to compare total cholesterol levels between serum samples analyzed immediately after collection and serum samples stored at 2–8°C for seven days. A quantitative analytical observational study with a repeated-measurement comparative design was conducted at Bhayangkara Hospital, Gorontalo, Indonesia, from June to July 2025. Fifteen paired serum samples were selected using accidental sampling. Total cholesterol concentrations were measured using the BioSystem BA200 automated chemistry analyzer. Differences between immediate and delayed analyses were evaluated using the paired-samples t-test after confirmation of data normality. Of the 15 samples, seven (47%) had normal cholesterol levels and eight (53%) had abnormal levels. The mean total cholesterol concentration increased slightly from 203 mg/dL to 206 mg/dL after seven days of refrigerated storage. However, the paired-samples t-test showed no statistically significant difference between the two conditions (p = 0.052). These findings indicate that serum storage at 2–8°C for up to seven days maintains total cholesterol stability and can be considered an acceptable pre-analytical practice when immediate laboratory analysis is not feasible.